Beauty's kingdom ebook A novel. - Roquelaure, A. N. (Sleeping Beauty, 2015)
Before E. L. James and Sylvia Day, there was Anne Rice: Discover  Beauty’s Kingdom , the fourth novel in the bestselling Sleeping Beauty series   Mega-bestselling author Anne Rice, writing as A. N. Roquelaure, returns to the mysterious kingdom of Queen Eleanor in this new chapter of her Sleeping Beauty series. When the great queen is reported dead, Beauty and Laurent return to the kingdom they left twenty years before. Beauty agrees to take the throne, but she insists that all erotic servitude be voluntary. Countless eager princes, princesses, lords, ladies, and commoners journey to Beauty’s realm, where she and her husband usher in a new era of desire, longing, and ecstasy. Provocative and stirring, Rice’s imaginative retelling of the Sleeping Beauty myth will be adored by her longtime fans and new readers of erotica just discovering the novels.   This book is intended for mature audiences.